An Effective Screening Method and a Reliable Screening Trait for Salt Tolerance of Brassica napus at the Germination Stage - Wu, Hui; Guo, Jianrong; Wang, Chengfeng; Li, Kailun; Zhang, Xiaowen; Yang, Zhen; Li, Maoteng; Wang, Baoshan (Frontiers in Plant Science, 2019)
Salinity is a major and complex abiotic stress that inhibits plant growth and reduces crop yield. Given the global increase in soil salinity, there is a need to develop salt-tolerant species. Brassica napus L. is an important oilseed crop with some level of salt tolerance. However, few studies have evaluated its salt tolerance thoroughly or screened for traits that can be reliably evaluated for salt tolerance. Here, we evaluated salt tolerance in 549 B. napus inbred lines with different genetic backgrounds using the membership function value of certain traits, including the germination rate, root and shoot length, root and shoot fresh weight, and total fresh weight. According to the evaluation criteria-mean MFV (membership function value), 50 highly salt-tolerant, 115 salt-tolerant, 71 moderately salt-tolerant, 202 salt-sensitive, and 111 highly salt-sensitive inbred lines were screened at the germination stage. We also developed a mathematical evaluation model and identified that the salt tolerance index of shoot fresh weight is a single trait that reliably represents the salt tolerance of B. napus germplasm at the germination stage. These results are useful for evaluating and breeding salt-tolerant B. napus germplasm.